The Relationship Between Reading Interest And Reading Literacy In Indonesian Folk Tales-Based English Learning - Yuswin Harputra; Yulia Rizki Ramadhani (Yayasan Kajian Riset dan Pengembangan RADISI, 2026)
Reading interest is an important affective factor influencing students' reading literacy, yet evidence in Indonesian EFL contexts using local culture-based materials remains limited. This study examined students' reading interest, English reading literacy, and the relationship between the two following Indonesian Folk Tales-based English learning. A quantitative correlational design was employed with 30 eighth-grade students of SMP Negeri 4 Angkola Timur selected through total sampling. Data were collected using a 22-item Reading Interest Questionnaire and a 35-item English Reading Literacy Test. Descriptive statistics, the Shapiro–Wilk normality test, and Pearson Product-Moment correlation were used for data analysis. The findings showed that students' reading interest was at a moderate-to-high level (M = 72.79%), while their English reading literacy was at a moderate level (M = 68.74%). Both variables were normally distributed (p > .05). Pearson correlation analysis revealed a significant moderate positive relationship between reading interest and English reading literacy (r = 0.497, p = 0.005), indicating that students with higher reading interest tended to achieve better reading literacy. These findings suggest that Indonesian Folk Tales-based learning can foster reading interest and support English reading literacy development. The study highlights the value of culturally relevant reading materials in promoting EFL literacy in Indonesian junior high schools.